Chemical Composition and Antibacterial Activity of Essential Oil of Prangos ferulacea (L.) Lindl. - H Amiri (Institue of Medicinal Plants, ACECR, 2007)
Background: The Prangos genus which belongs to Umbelliferae family is represented 15 species in Iran. Jashir (Prangos ferulacea Lindl.) is long and permanent herb which is mainly used as rich herb in animal feeding. Moerover the essential oils were mainly used in nutrative and pharmaceutical industries and antibacterial agents. Objective: Identification of chemical composition of essential oil of Prangos ferulacea grown in Lorestan province and its comparison with other regions, and to study antibacterial activity. Methods: This plant was collected from Broujerd mountains of Lorestan province in Iran. Voucher specimens were deposited at the herbarium of Natural Resource and Agriculture Center of Lorestan Province (NO: 5783). The air-dried aerial parts were subjected to hydrodistillation method. Identification of essential oil costitiuents was made by GC and GC/MS. After drilling wells on medium oils dissolved in hexane and 40μL from solutions in each well was poured. Results: The yield of essential oils obtained by hydrodistillation from dried plant material was 1.6% w/w. The main constituent of this oil were α-pinene (36.6%) and β-pinene (31.1%). The results of the antibacterial activity showed that the oil was active against of most of the positive and negative bacteria specially Staphyllococcus aureus Conclusion: A large prcentage of the oil was composed of hydrocarbone monoterpens and only identified sesquiterpen compound is β-caryophyllene (3.1 %). Sefidkon and Kuznetsova investigations on analysis of the essential oil of aerial parts and fruits from Jashir demonesterated similarities and differenes with our study. Antibacterial activity of the oil was probably attributed to large content of monoterpene especially α-pinene.